The Financial Distress, COVID-19 Pandemic, and Female Commissioner Effectiveness - Nurdiana; Sumarsono, Hadi; Rapini, Titi (AKRUAL: JURNAL AKUNTANSI, 2025)
Abstract Introduction/Main Objectives: The purpose of this research was to determine effect of female commissioner and COVID-19 pandemic on financial distress in property and real estate companies listed on Indonesia Stock Exchange from 2017 to 2022 with liquidity, leverage, operating capacity, and firm size as control variables. Background Problems: Competition and development of property and real estate companies that fluctuate cause high costs that must be faced by companies, but companies that are unable to deal with high costs will experience unstable financial conditions and potentially experience financial distress. Research Methods: Logistic regression analysis method was used in analysing this research. There were 43 companies as samples with the research period 2017-2022 so that sample of 258 observation data was obtained. Finding/Results: Female commissioner significantly effect on financial distress, while COVID-19 pandemic has no effect on financial distress. Conclusion: The existence of female commissioner is worthy of company’s attention because they tend to be careful and make low-risk decisions. Female commissioner is considered capable of providing signals about condition of the company and minimize conflicts of interest to reduce risk of financial distress.